Recent Developments of Interdealer Brokerage in the Japanese Secondary Bond Markets - Maru, Junko; Takahashi, Toshiharu (Journal of Financial and Quantitative Analysis, 1985)
The large volume of government bonds issued since 1975 has been a strong driving force for structural change in the Japanese bond markets during the last decade. The increasing amount of outstanding government bonds has made the trading volume in the secondary market increase rapidly, accompanied with the development of interdealer trading.